A comparative study on direct planted and transplanted menthol mint (Mentha arvensis L.) under integrated nutrient management - D Patra, Sukhmal Chand, M Anwar, Kambod Singh, D (Journal of Spices and Aromatic Crops, 2004)
An experiment was conducted at Lucknow (Uttar Pradesh) to assess crop productivity and economics of direct planted and transplanted menthol mint (Mentha arvensis) in sandy loam soil, under integrated nutrient management. The treatments consisted of five different combinations of farmyard manure (FYM) and inorganic fertilizers (NPK). Herb and essential oil yield was maximum with application of 133:40:40 kg NPK ha-tand 6.7 t FYM ha-t in both the methods of planting. However, the crop established with direct planting of suckers was more profitable than the transplanted crop. Net returns were 269% and 213% higher over control, with combined application of 133:40:40 kg NPK ha·t and 6.7 t FYM ha-t in direct and transplanted crop, respectively, during the first year of experimentation and 305% and 232%, respectively, during the second year. Dry matter production and NPK uptake were also maximum in the same treatment in both the methods of planting. Maximum Nand P uptake was recorded in sole application of inorganic fertilizers (200:60:60 kg NPK ha-t) and maximum K uptake was observed under application of 100:30:30 kg NPK ha-t and 10 t FYM ha-t in direct planted crop during the first year. Post-harvest soil characteristics like organic carbon, available NPK, Fe and Zn were higher during the second year, while a reverse trend was observed for soil pH.